Hydrogen Jet-Fire: Accident Investigation and Implementation of Safety Measures for the Design of a Downstream Oil Plant - Daniele Cermelli; Fabio Curro; Tomaso Vairo; Bruno Fabiano (Chemical Engineering Transactions, 2018)
As amply known, hydrogen plays a very significant role in the process industry exerting a vital functionality in oil refineries, namely for secondary level refining units such hydro-treating and hydrocracking sections. This paper starts from a statistical analysis on hydrogen accidents and a thorough investigation on the sequence and causes of an accident involving a hydrogen leakage in a downstream oil industry. We present some key features of the accident and comment some practical implications for setting up risk reduction options at the plant level. The applicative phase of the paper states the main prevention strategies and suggest possible mitigation measures for hydrogen leaks events, discussing some practical solutions applied in the design of a large refinery. The experience and lessons learned gained from the event investigation and the comparison of the accident with the predictions of the safety report leads to the formulation of proposals and design modifications aiming at preventing or at least minimizing the consequences.